2005
DOI: 10.1093/eurpub/cki053
|View full text |Cite
|
Sign up to set email alerts
|

Repeat prescriptions: refill adherence in relation to patient and prescriber characteristics, reimbursement level and type of medication

Abstract: Refill non-adherence includes both under- and oversupplying and may vary due to different attitudes between prescribers and between patients. Different therapeutic indications and reimbursement systems are other apparent causes. These observations should be considered in programs aiming to assist patients in following medication prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 12 publications
2
62
2
Order By: Relevance
“…Moreover, because adherence to prescribed drug treatment is low (Andersson et al, 2005) and irregular administration of these drugs is common we choose a liberal limit of 12 months, and there were no significant differences when compared to a 6 month cut-off limit. Circumstances which could imply a medical intention of drug intake in the absence of a recent dispense (i.e.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Moreover, because adherence to prescribed drug treatment is low (Andersson et al, 2005) and irregular administration of these drugs is common we choose a liberal limit of 12 months, and there were no significant differences when compared to a 6 month cut-off limit. Circumstances which could imply a medical intention of drug intake in the absence of a recent dispense (i.e.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…24 These differences in adherence are often attributed to the quality of the patient-provider interactions; [25][26][27] the salient nontherapeutic features of the drugs prescribed, including the complexity of regimens; 28,29 and the occurrence of unpleasant sideeffects or drug interactions. [30][31][32][33] In short, filling a prescription and taking the medication as prescribed is a complex health behavior determined by the patient's perceptions of drug costs and benefits and mediated by various provider and health system attributes. 34 Much of the literature on medication adherence assumes a rational decision-making process where patients weigh the perceived therapeutic benefits of each medication against the cost of filling the prescription and restrict use of high-cost, lowbenefit medications.…”
mentioning
confidence: 99%
“…They may for example unintentionally overuse the same medication (168,169), which increases the risk to experience ADRs. Previous studies have found that oversupply of medications was found in up to 53% of patients taking antidiabetics (152,(170)(171)(172)(173), up to 52% with antihypertensive medications (152,170,174,175), and up to 35% with lipid lowering medications (152,170).…”
Section: Non-adherence To Long-term Medicationsmentioning
confidence: 97%
“…For example, non-adherence has been found to be higher for long-term than short term therapies (145), for preventive than curative therapies, and for asymptomatic conditions, such as hypertension (145,146 Refill adherence is one of the most used methods to measure adherence, and has been correlated with other measures of adherence (151). The act of refilling prescribed medications and the frequency of medication refills reflect different aspects of a patient's adherence behaviour, and can be divided into adequate refill adherence, undersupply and oversupply (152). Refill adherence is only considered as a proxy measure of adherence if patients obtain their medications within a closed pharmacy system, such as in countries with universal medication coverage (147).…”
Section: Non-adherence To Long-term Medicationsmentioning
confidence: 99%